Determination of structural, mechanical, thermal and magnetic properties of Cr based new quaternary Heusler alloys with GGA and GGA+U. (4th January 2021) - Zafar, M; Amjad, Swera; Shakil, M; Gillani, S S A; Arshad, Hafsa; Tahir, M B; Tariq, N H
Abstract: Structural, mechanical, thermal and magnetic properties of Quaternary Heusler alloys (QHA) CrFeTiZ (Z = Al, Si, Ge, Ga) are determined by employing full potential - linearized augmented plane wave (FP-LAPW) method using density functional theory (DFT). Geometry optimization of all these QHAs is accomplished and Type 2 is found the most stable. Elastic parameters reveal the mechanical stability and ductile behavior of all considered alloys. The calculated Debye Temperature ( θ D ) assured that these alloys can be appropriate for high temperature devices due to high thermal conductivity ( κ ) and melting temperature (Tmelt ). All these compounds are half metallic (HM) in nature as the band gap (Eg ) is present in one spin orientation. The values of Eg for CrFeTiAl and CrFeTiGa are 0.68 eV and 0.86 eV respectively which are obtained by employing generalized gradient approximation (GGA) while Hubbard parameter (U) with GGA is used to calculate Eg of CrFeTiGe and CrFeTiSi and the Eg are 0.93 eV and 0.9 eV. The calculated magnetic moment (MM) of CrFeTiZ (Z = Al, Si, Ge, Ga) alloys agrees with Slater-Pauling rule (SPR). From the obtained results it is envisaged that these materials are suitable candidates for spintronic and high temperature devices.